princeofwetlot
how to solve \[2(2xy + 4y 3)dx + (x+2)^2 dy = 0\] via the Integrating Factor Method (Linear Differential Equations)



This Question is Closed

saifoo.khan
Best Response
You've already chosen the best response.
0
@dpaInc

princeofwetlot
Best Response
You've already chosen the best response.
0
@Zarkon

saifoo.khan
Best Response
You've already chosen the best response.
0
@satellite73

princeofwetlot
Best Response
You've already chosen the best response.
0
@turingtest

Chlorophyll
Best Response
You've already chosen the best response.
1
2( 2xy + 4y −3 )dx + (x+2)² dy = 0
> dy/dx =  4y/(x +2) + 6/ (x+2)²
4y/(x +2) + dy/dx = 6/ (x+2)²
Let I = e^ 4∫ dx/(x +2) = e^ [ ln (x+2)^4 ] = ( x+2) ^4
=> ( x+2) ^4* y = 6 ∫ ( x+2) ^4 dx/ (x+2)²
= 6 ∫ (x+2)² dx

Chlorophyll
Best Response
You've already chosen the best response.
1
Can you continue from here?